Pembuatan Indeks Jurnal Ilmiah di Perpustakaan Institut Teknologi Padang - Sari, Intan Permata; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
This paper discussed about creating indexes of scientific journals in the Library of the Institute of Technology Padang. This paper aims to describe how the manufacturing index ilmial journals in the Library Institute of Technology Padang. The method used is descriptive method with data collection through observation or direct observation to the Library Institute of Technology Padang, interviews, and literature. From the observation of interviews conducted at the Institute of Technology Library Padang, collected as many as 19 journals with the number of 413 articles. Based on the results of the discussion in the manufacturing index of scientific journals in the Library of the Institute of Technology of Padang, we can conclude several steps taken indexing scientific journals such as: 1) The initial observations of the document, which is observing the document to be indexed and collect the necessary data; 2) make a description, which was to determine the author's name, title of article, journal titles containing the article, volume (number), month and year of issue of the journal, and page number of the journal that published articles; and 3) typing index.Keyword: index; journal; Institute of Technology PadangÂ